Papel de antígenos contendo repetições de aminoácidos na infecção pelo Trypanosoma cruzi e sua utilização para sorodiagnóstico da doença de Chagas - Nailma Silva Aprigio dos Santos (2016)
Proteins containing repetitive amino acid sequences are abundantly present in different parasitic protozoa. Data from the literature indicate that these repetitions function as a mechanism of parasite evasion of the host immune system. To test this hypothesis, we are investigating two proteins of T.cruzi: TcL7a and trans-sialidase. The TcL7a is a ribosomal protein, identified in an Immunoscrenning with serum of patients with Chagas disease and that presents homology with other proteins L7a eukaryotes. However, unlike other eukaryotic L7a proteins, the T. cruzi L7a protein contains a domain with Ala-Lys-Pro amino acid repeats in its N-terminal portion. The immunization with only the repetitive motive of TcL7a and subsequent challenge with T.cruzi tripomastigotas forms caused an exacerbation of parasitemia compared to non-immunized animals, suggesting that repetitions negatively modulate the immune response in order to favor infection. Transsialidase (TS) is also a T. cruzi protein that contains amino acid repeats and has the function of transferring sialic acid residues from the host to mucins on the surface of the parasite, a process related to host cell invasion and to immune system escape.Recent results from our group indicate that the repetitions of 12 amino acids present in the C-terminal portion of some members of the TS family contribute to the virulence of the parasite. To investigate this hypothesis, recombinant versions of this protein were generated: TS in full form, with the deletion of the repetitive part and only the repetitive portion of TS. All proteins were expressed in bacteria and the protein containing only SAPA repeats was purified for use in immunization experiments that will still be performed. Since the repetitions of different proteins of T. cruzi are targets of the immune response, we propose the use of antigens containing these reasons for the development of diagnostic tests for Chagas disease. In order to obtain a more sensitive test, these regions were linked in gold nanoparticles, which were able to interact with the two antigens and this complex will be tested with the serum of patients with Chagas disease.